The economic impacts of wheelchair use: Evidence from Central Java, Indonesia - Agnes Bhakti Pratiwi; Hermawati Setiyaningsih; Rizki Mahardya; Firdaus Hafidz; Diah Ayu Puspandari (Journal of Community Empowerment for Health, 2019)
An estimated 10% of the global population has disabilities, and 1 out of 10 require wheelchairs. Although imperative, the provision of wheelchair services remains challenging, especially in low resource settings. Interacting barriers in availability of wheelchair services and healthcare access can negatively affect households of people with disabilities in productivity and obtaining income. The availability of wheelchair services can potentially lessen the related economic burden. However, to date there is limited evidence concerning the economic gain of the wheelchair users in Indonesia. This study aims to analyze the economic impact of using wheelchairs on households in rural Central Java Province, Indonesia. Economic gains of wheelchair users were measured using a cross-sectional survey in Central Java, Indonesia during 2017. The questionnaires consisted of three main sections, namely general information, socio-economic information before and after using adaptive wheelchair, and income and spending related information. A total of 60 adaptive wheelchair users and parent proxy completed the questionnaires. More than half (55%) of the respondents were male, became impaired in 1998, and used an adaptive wheelchair starting in 2009. Medical conditions of the respondents related to need for a wheelchair are cerebral palsy (29%), paraplegia (29%), and polio (15.5%). Three-fourths of the respondents were working in the informal sector. On average, there is a significant increase of Rp. 217,662 in monthly household income between before and after using a wheelchair. However, there was no significant difference in spending before and after using a wheelchair. Respondents feel that using a wheelchair is beneficial particularly in mobility and helping in their activities. Wheelchair use can increase the income of households with disability. Clients responded that there have been several aspects which need further support, including skills improvement, employment generation for people with disabilities, and adequate public transportation facilities.